Modular control of gait after incomplete spinal cord injury: differences between sides - Pérez-Nombela, S; Barroso, F; Torricelli, D; de los Reyes-Guzmán, A; del-Ama, A J; Gómez-Soriano, J; Pons, J L; Gil-Agudo, Á (Spinal cord, 2017)
Study design: This is an analytical descriptive study. Objectives: The main goal of this study was to compare the modular organization of bilateral lower limb control in incomplete spinal cord injury (iSCI) patients during overground walking, using muscle synergies analysis. The secondary goal was to determine whether the similarity between the patients and control group correlate with clinical indicators of walking performance. Setting: This study was conducted in National Hospital for Spinal Cord Injury (Toledo, Spain). Methods: Eight iSCI patients and eight healthy subjects completed 10 walking trials at matched speed. For each trial, three-dimensional motion analysis and surface electromyography (sEMG) analysis of seven leg muscles from both limbs were performed. Muscle synergies were extracted from sEMG signals using a non-negative matrix factorization algorithm. The optimal number of synergies has been defined as the minimum number needed to obtain variability accounted for (VAF) ⩾90%. Results: When compared with healthy references, iSCI patients showed fewer muscle synergies in the most affected side and, in both sides, significant differences in the composition of synergy 2. The degree of similarity of these variables with the healthy reference, together with the composition of synergy 3 of the most affected side, presented significant correlations ( P <0.05) with walking performance. Conclusion: The analysis of muscle synergies shows potential to detect differences between the two sides in patients with iSCI. Specifically, the VAF may constitute a new neurophysiological metric to assess and monitor patients’ condition throughout the gait recovery process.